The Byzantine Empire - DeCarlo, Carolyn (Empires in the Middle Ages., 2018)
Chronicles the centuries-long rise and fall of the powerful Byzantine Empire, including important political events, leaders, culture, society, and wars. Includes illustrations and photographs, a glossary, sources for further information, and an index.